Improvement of hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) by enzyme-digested poultry by-product: Growth performance, amino acid and peptide transport capacity, and intestinal morphology - Yang, Xuanyi; Zhao, Xumin; Wang, Guanghui; Dong, Xiaohui; Yang, Qihui; Liu, Hongyu; Zhang, Shuang; Tan, Beiping; Chi, Shuyan (Frontiers in Nutrition, 2022)
Background At present, fish meal (FM) resources are in short supply, and competition for food between humans and animals is becoming increasingly critical. Finding non-grain protein sources that can replace FM is the key to solving the rapid development of aquaculture. Methods Seven trial diets were prepared with 0 g/kg (EP0), 30 g/kg (EP3), 60 g/kg (EP6), 90 g/kg (EP9), 120 g/kg (EP12), 150 g/kg (EP15), and 180 g/kg (EP18) of enzyme-digested poultry by-product meal (EPBM) by replacing of FM. A total of 630 hybrid groupers (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) were equally portioned into 21 tanks. At 8:00 and 16:00 each day, groupers were fed until they were full for a cumulative period of 8 weeks. Results The results showed that 30 g/kg of EPBM significantly increased the rates of weight gain and special growth (P < 0.05). Significantly higher activities of serum glutamic pyruvic transaminase, glutamic oxaloacetic transaminase, catalase, and superoxide dismutase were observed in the EP3 group (P < 0.05). The categories and numbers of the top 10 dominant bacteria in the phylum and genus levels were not significantly influenced by feed (P > 0.05). In the proximal intestine and distal intestine, there were significantly higher expressions of SNAT3, LAAT1, CAT2, and CAT1 in the EP3 group compared with the EP0 group (P < 0.05). In the EP3 group, the expressions of PepT1, LAAT1, B0, +AT, and CAT2 were significantly increased in MI than those in all other groups (except the EP0 group, P < 0.05). Conclusion When FM was replaced by 30 g/kg of EPBM, growth performance, antioxidant capacity, and the ability to transport amino acids and peptides of hybrid grouper were significantly improved.